Development of a Bone-Mimetic 3D Printed Ti6Al4V Scaffold to Enhance Osteoblast-Derived Extracellular Vesicles’ Therapeutic Efficacy for Bone Regeneration - Man, Kenny; Brunet, Mathieu Y.; Louth, Sophie; Robinson, Thomas E.; Fernandez-Rhodes, Maria; Williams, Soraya; Federici, Angelica S.; Davies, Owen G.; Hoey, David A.; Cox, Sophie C. (Frontiers in Bioengineering and Biotechnology, 2021)
Extracellular vesicles (EVs) are considered promising nanoscale therapeutics for bone regeneration. To date, EVs are typically procured from cells on 2D tissue culture plastic, an artificial environment that limits cell growth and does not replicate in situ biochemical or biophysical conditions. This study investigated the potential of 3D printed titanium scaffolds coated with hydroxyapatite to promote the therapeutic efficacy of osteoblast-derived EVs. Ti6Al4V titanium scaffolds with different pore sizes (500 and 1000 µm) and shapes (square and triangle) were fabricated by selective laser melting. A bone-mimetic nano-needle hydroxyapatite (nnHA) coating was then applied. EVs were procured from scaffold-cultured osteoblasts over 2-weeks and vesicle concentration was determined using the CD63 ELISA. Osteogenic differentiation of human bone marrow stromal cells (hBMSCs) following treatment with primed EVs was evaluated by assessing alkaline phosphatase activity, collagen production and calcium deposition. Triangle pore scaffolds significantly increased osteoblast mineralisation (1.5-fold) when compared to square architectures (P ≤ 0.001). Interestingly, EV yield was also significantly enhanced on these higher permeability structures (P ≤ 0.001), in particular (2.2-fold) for the larger pore structures (1000 µm). Furthermore osteoblast-derived EVs isolated from triangular pore scaffolds significantly increased hBMSCs mineralisation when compared to EVs acquired from square pore scaffolds (1.7-fold) and 2D culture (2.2-fold) (P ≤ 0.001). Coating with nnHA significantly improved osteoblast mineralisation (>2.6-fold) and EV production (4.5-fold) when compared to uncoated scaffolds (P ≤ 0.001). Together, these findings demonstrate the potential of harnessing bone-mimetic culture platforms to enhance the production of pro-regenerative EVs as an acellular tool for bone repair.